MYC‐binding lncRNA EPIC1 promotes AKT‐mTORC1 signaling and rapamycin resistance in breast and ovarian cancer. Issue 10 (18th August 2020) - Wang, Yifei; Zhang, Min; Wang, Zehua; Guo, Weiwei; Yang, Da
Abstract: AKT‐mTORC1 (mammalian target of rapamycin complex 1) signaling pathway plays a critical role in tumorigenesis and can be targeted by rapamycin. However, the underlying mechanism of how long noncoding RNA (lncRNAs) regulate the AKT‐mTORC1 pathway remains unclear. EPIC1 (epigenetically‐induced lncRNA 1) is a Myc‐binding lncRNA, which has been previously demonstrated to be overexpressed in multiple cancer types. In a pathway analysis including 4962 cancer patients, we observed that lncRNA EPIC1 expression was positively correlated with the AKT‐mTORC1 signaling pathway in more than 10 cancer types, including breast and ovarian cancers. RNA‐seq analysis of breast and ovarian cancer cells demonstrated that EPIC1‐ knockdown led to the downregulation of genes in the AKT‐mTORC1 signaling pathway. In MCF‐7, OVCAR4, and A2780cis cell lines, EPIC1 knockdown and overexpression, respectively, inhibited and activated phosphorylated AKT and the downstream phosphorylation levels of 4EBP1 and S6K. Further knockdown of Myc abolished the EPIC1 ′s regulation of AKT‐mTORC1 signaling; suggested that the regulation of phosphorylation level of AKT, 4EBP1, and S6K by EPIC1 depended on the expression of Myc. Moreover, EPIC1 overexpressed MCF‐7, A2780cis, and OVCAR4 cells treated with rapamycin showed a significant decreasing in rapamycin mediated inhibition of p‐S6K and p‐S6 comparing with the control group. In addition, Colony Formation assay and MTT assay indicated that EPIC1 overexpression led to rapamycin resistance in breast and ovarian cancer cell lines. Our results demonstrated the lncRNA EPIC1 expression activated the AKT‐mTORC1 signaling pathway through Myc and led to rapamycin resistance in breast and ovarian cancer.